MANAJEMEN GURU DALAM MERESPON SISWA MENGGUNAKAN MODEL PEMBELAJARAN LURING DAN DARING, DI MASA PANDEMI COVID-19 - Novia Hendra; Muhammad Giatman; Ernawati Ernawati (STKIP Pesisir Selatan, 2022)
The purpose of this research is to find out the teacher's response to offline and online learning, especially in the long term as we are currently facing with the Corona Virus (COVID-19) which has not stopped. Through questionnaire response analysis using offline and online learning models, the research sample is teachers who teach at the Vocational High School level, both from public and private schools in the Padang city area. The instrument used is a questionnaire distributed online using the ms.form link. Based on the data obtained that the implementation of offline and online learning has been carried out effectively, it can be seen from the teacher's response to offline and online learning using a learning model, namely 40% of teachers said it was very good, 30% said it was good, 20% said it was not good, and 10% said very not good at processing offline and online learning models. With the results found from the management of educator readiness in offline and online learning in the future, it can be anticipated to be more effective by looking at the shortcomings and obstacles found in the field through this research.